2018
DOI: 10.1016/j.biortech.2017.10.069
|View full text |Cite
|
Sign up to set email alerts
|

A life cycle assessment of options for producing synthetic fuel via pyrolysis

Abstract: The aim of this study was to investigate the sustainability of producing synthetic fuels from biomass using thermochemical processing and different upgrading pathways. Life cycle assessment (LCA) models consisting of biomass collection, transportation, pre-treatment, pyrolysis and upgrading stages were developed. To reveal the environmental impacts associated with greater post-processing to achieve higher quality fuels, six different bio-oil upgrading scenarios were analysed and included esterification, ketoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Vienescu et al (2018) studied the use of pyrolysis to produce synthetic fuels via an LCA approach. Despite the promising results, similar LCA studies must consider the wide range of environmental impacts that occur during the synthesis production.…”
Section: Plastic Waste Management Options and Processesmentioning
confidence: 99%
“…Vienescu et al (2018) studied the use of pyrolysis to produce synthetic fuels via an LCA approach. Despite the promising results, similar LCA studies must consider the wide range of environmental impacts that occur during the synthesis production.…”
Section: Plastic Waste Management Options and Processesmentioning
confidence: 99%
“…This study suggested using standardized methods such as Life Cycle Assessment (LCA) to evaluate the environmental impacts of a product's life cycle that covers most activities involved in BSC. Many LCAs have been conducted for biomass‐based products (Liao et al, 2020; Peters et al, 2015; Vienescu et al, 2018) and the integration of LCA to BSC optimization has been explored (Yue et al, 2014). One major challenge of conducting LCA for bioenergy systems, especially for new technologies or feedstock, is the lack of Life Cycle Inventory (LCI) data (e.g., energy consumption and air emissions; Yao & Masanet, 2018), and AI could be a promising tool to address this challenge.…”
Section: Applications Of Artificial Intelligence To Bioenergy Systemsmentioning
confidence: 99%
“…The simplicity, maturity, and low cost of pyrolysis bio-oil production must therefore be balanced against the complexity and cost of its upgrading. The GHG emissions reductions must also be calculated accordingly, with poorly devised upgrading scenarios potentially raising life cycle emissions beyond that of fossil diesel ( Vienescu et al., 2018 ).…”
Section: Bio-oilmentioning
confidence: 99%